The handbook of polyhydroxyalkanoates. Volume 1, Microbial biosynthesis and feedstocks - Koller, Martin (Researcher) (Boca Raton : CRC Press, 2020)
The first volume of the "Handbook of Polyhydroxyalkanoates (PHA): Microbial Biosynthesis and Feedstocks" focusses on feedstock aspects, enzymology, metabolism and genetic engineering of PHA biosynthesis. It addresses better understanding the mechanisms of PHA biosynthesis in scientific terms and profiting from this understanding in order to enhance PHA biosynthesis in bio-technological terms and in terms of PHA microstructure. It further discusses making PHA competitive for outperforming established petrol-based plastics on industrial scale and obstacles for market penetration of PHA. Aimed at professionals and graduate students in Polymer (plastic) industry, wastewater treatment plants, food industry, biodiesel industry, this book Covers the intracellular on-goings in PHA-accumulating bacteria Assesses diverse feedstocks to be used as carbon source for PHA production including current knowledge on PHA biosynthesis starting from inexpensive waste feedstocks Summarizes recent relevant results dealing with PHA production from various organic by-products Presents the key elements to understand and fine-tune the microstructure and sequence-controlled molecular architecture of PHA co-polyesters Discusses the use of CO-rich syngas, sourced from various organic waste materials, for PHA biosynthesis
OCLC-licensed vendor bibliographic record.
Keywords: Poly-beta-hydroxyalkanoates.; MEDICAL / Biotechnology; SCIENCE / Biotechnology; TECHNOLOGY / Engineering / Chemical & Biochemical